Blow-up results for damped wave equation with fractional Laplacian and non linear memory - HADJ KADDOUR, Tayeb; HAKEM, Ali (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
This paper is devoted to find the critical exponent in Fujita’s sense and to prove the blow-up results of solutions for the damped equation with fractional Laplacian and nonlinear memory. Mathematics Subject Classification (2010): 26A33, 35K55, 74G25, 74H35. Received 02 February 2020; Accepted 10 May 2020.